Pharmacokinetic Analysis of Mycophenolate Mofetil and Enteric-Coated Mycophenolate Sodium in Calcineurin Inhibitor–Free Renal Transplant Recipients. Issue 3 (June 2016) - Graff, Jochen; Scheuermann, Ernst-Heinrich; Brandhorst, Gunnar; Oellerich, Michael; Gossmann, Jan
Abstract : Background: Considerable interest exists in identifying calcineurin inhibitor (CNI)-free and thus, less-toxic immunosuppressive regimens, with mycophenolic acid (MPA)–based treatments being a suitable approach. Because pharmacokinetic analyses of MPA treatments in stable CNI-free renal transplant recipients are lacking, the authors aimed at comparing the steady-state pharmacokinetic characteristics of MPA in patients on stable treatment with mycophenolate mofetil (MMF) or enteric-coated mycophenolate sodium (EC-MPS) plus prednisone (⩽5 mg/d). Methods: In the prospective, nonrandomized, open-label study, patients with stable transplant function since ≥6 months received their routine single dose of either MMF (n = 12) or EC-MPS (n = 11). The MPA plasma concentration was recorded over 12 hours. Parameters assessed were predose MPA concentration ( C 0 ), postdose minimum and maximum concentration ( C min and C max ), time to maximum concentration ( T max ), and area under the concentration–time curve (AUC) for the 12-hours of exposure (AUC0-12 ). Results: Baseline characteristics were comparable between both the groups. Consistent with enteric coating, the mean T max was significantly longer after the intake of EC-MPS compared with MMF (2.2 versus 0.8 hours; P = 0.0002). The exposure measures C min, C max, and AUC0-12 were not significantly different despite the higher mean MPA equivalent dose in patients receiving MMF compared with those receiving EC-MPS (85% versus 64% of the recommended single dose, respectively). Exposures as reflected by the median AUC0-12 values were 50.7 and 58.7 mg·h −1 ·L −1 with MMF and EC-MPS, respectively ( P = 0.340). All patients achieved a target AUC of >30 mg·h −1 ·L −1, and 61% had an AUC of >50 mg·h −1 ·L −1 . Conclusions: The study provides first results on the steady-state pharmacokinetics of the 2 MPA drugs in CNI-free immunosuppressant regimens. Pharmacokinetic parameters measured in this study under real-life conditions were comparable in patients receiving MMF or EC-MPS.